Analisis Faktor Kesulitan Belajar Siswa Mata Pelajaran Pembuatan Busana Kerja Kelas XII Tata Busana SMK NU 2 Blawirejo Kedungpring - Dyah Ayu Vimastuti; Imami Arum Tri Rahayu; Peppy Mayasari; Mita Yuniati (LPPM Politeknik Pratama, 2024)
This study aims to determine (1) the learning difficulties experienced by students in the competence of making work clothes in class XII Cosmetology SMK NU 2 Blawirejo Kedungpring in terms of; a) Affective aspects b) Cognitive aspects c) Psychomotor aspects. (2) the most dominant factor of learning difficulties in the subject of making work clothes in class XII SMK NU 2 Blawirejo Kedungpring from; a) Affective aspects b) Cognitive aspects c) Psychomotor aspects This research is descriptive research. This research was conducted in the odd semester of the 2023/2024 academic year at SMK NU 2 Blawirejo Kedungpring. The population used in this study were 18 students. The data collection technique used a questionnaire with a guttman scale. The results showed that (1) the learning difficulties experienced by students were as follows: (1) the learning difficulties experienced by students are as follows: (2) the most dominant factor of learning difficulties in making work clothes is the cognitive factor, which is included in the high category, namely 12 (69%) experiencing difficulties and the psychomotor aspect is included in the high category, namely 12 (67%) experiencing difficulties (2) the most dominant factor of learning difficulties in making work clothes is the cognitive factor.